THE INFLUENCE OF FOMO AND YOLO ON FINANCIAL BEHAVIOR AMONG GENERATION Z IN BIMA CITY - Aliah Pratiwi; Nurul Huda; Aris Munandar; Nafisah Nurulrahmatiah (Procuratio : Jurnal Ilmiah Manajemen, 2026)
This study examines the influence of fear of missing out (FoMO) and the You Only Live Once (YOLO) lifestyle on the financial behavior of Generation Z in Bima City. The study is positioned in behavioral finance and consumer behavior by integrating the Theory of Planned Behavior, self-determination theory, mental accounting, and the financial management behavior perspective. A quantitative explanatory design was applied using a survey of 120 Generation Z respondents aged 18-27 years who lived in Bima City and actively used social media or digital financial services. The data were analyzed using partial least squares structural equation modeling (PLS-SEM) with SmartPLS 4. The findings indicate that FoMO has a negative and significant effect on financial behavior, while YOLO lifestyle also has a negative and significant effect. The structural model explains 56.3% of the variance in financial behavior, indicating substantial explanatory power for a two-predictor behavioral model. The results imply that emotional urgency, social comparison, trend-following consumption, and present-oriented spending weaken budgeting discipline, saving consistency, and debt control among young consumers. This study contributes to the literature by contextualizing FoMO and YOLO as socio-digital determinants of financial behavior among Generation Z in a local Indonesian city. Practically, the findings highlight the need for financial education programs that address not only financial literacy but also emotional self-regulation, digital consumption pressure, and social media-driven spending habits. Penelitian ini menguji pengaruh fear of missing out (FoMO) dan gaya hidup You Only Live Once (YOLO) terhadap perilaku keuangan Generasi Z di Kota Bima. Penelitian ini menggunakan desain kuantitatif eksplanatori dengan survei terhadap 120 responden Generasi Z berusia 18-27 tahun yang berdomisili di Kota Bima dan aktif menggunakan media sosial atau layanan keuangan digital. Data dianalisis menggunakan partial least squares structural equation modeling (PLS-SEM) dengan SmartPLS 4. Hasil penelitian menunjukkan bahwa FoMO memiliki pengaruh negatif dan signifikan terhadap perilaku keuangan, sementara gaya hidup YOLO juga memiliki pengaruh negatif dan signifikan. Model struktural menjelaskan 56,3% varians dalam perilaku keuangan, menunjukkan daya penjelas yang substansial untuk model perilaku dua prediktor. Hasil tersebut menyiratkan bahwa urgensi emosional, perbandingan sosial, konsumsi mengikuti tren, dan pengeluaran berorientasi masa kini melemahkan disiplin penganggaran, konsistensi menabung, dan pengendalian utang di kalangan konsumen muda. Studi ini berkontribusi pada literatur dengan mengkontekstualisasikan FoMO dan YOLO sebagai penentu sosial-digital perilaku keuangan di kalangan Generasi Z di sebuah kota lokal di Indonesia. Secara praktis, temuan tersebut menyoroti perlunya program pendidikan keuangan yang tidak hanya membahas literasi keuangan tetapi juga pengaturan diri emosional, tekanan konsumsi digital, dan kebiasaan pengeluaran yang didorong oleh media sosial.